2017
DOI: 10.3390/ijerph14091040
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Socioeconomic Vulnerability, Psychosocial Services, and Social Service Spending on Family Reunification: A Multilevel Longitudinal Analysis

Abstract: Socio-environmental factors such as poverty, psychosocial services, and social services spending all could influence the challenges faced by vulnerable families. This paper examines the extent to which socioeconomic vulnerability, psychosocial service consultations, and preventative social services spending impacts the reunification for children placed in out-of-home care. This study uses a multilevel longitudinal research design that draws data from three sources: (1) longitudinal administrative data from Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Across most communities, socioeconomically vulnerable mothers have unmet health needs [37]. Socioeconomic vulnerability is influenced by a combination of risk factors at both the individual level and environmental level [38]. Both individual and community poverty are particularly important, impacting access to factors such as housing, food, transportation, clothing, health care, and education that have both immediate and future consequence to life course trajectories [38,39].…”
Section: Study Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Across most communities, socioeconomically vulnerable mothers have unmet health needs [37]. Socioeconomic vulnerability is influenced by a combination of risk factors at both the individual level and environmental level [38]. Both individual and community poverty are particularly important, impacting access to factors such as housing, food, transportation, clothing, health care, and education that have both immediate and future consequence to life course trajectories [38,39].…”
Section: Study Focusmentioning
confidence: 99%
“…Socioeconomic vulnerability is influenced by a combination of risk factors at both the individual level and environmental level [38]. Both individual and community poverty are particularly important, impacting access to factors such as housing, food, transportation, clothing, health care, and education that have both immediate and future consequence to life course trajectories [38,39]. Socioeconomically vulnerable mothers are ideal to consider in network health literacy as they have known health literacy challenges [40], and often tend to their own health needs as well as those of their children, parents, and others [41].…”
Section: Study Focusmentioning
confidence: 99%
“…They explain further that parents with low socioeconomic status were the least likely to reinforce safety concepts at home and also the least likely to provide protection. The study by Esposito et al (2017) also revealed that socioeconomic vulnerabilities decrease parents' ability to provide safe and adequate environment for their children's protection, leading to a high risk of out-of-home placement for children of such families.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Briggs and Hawkins (1996) notes that the socioeconomic status of parents significantly influence children's safety and protection, and that parents with low socioeconomic status were the least likely to reinforce safety concepts at home and also the least likely to provide protection. Esposito et al (2017) also revealed that socioeconomic vulnerabilities decrease parents' ability to provide safe and adequate environment for their children's protection, leading to a high risk of out-of-home placement for children of such families. Gans (2019) observed that regardless of any age that one intends to become parent, one thing to know is that parenting comes with challenges.…”
Section: Socioeconomic Status Of Parents and Children's Wellbeingmentioning
confidence: 99%
“…Rate ratio modelling of a large sample of birth rate data in New Zealand identified that Maori children, particularly those exposed to more risk factors, were more likely to experience abuse or neglect when compared to non‐Maori children (Cram, Gulliver, Ota, & Wilson, ). Living with poverty, as a risk factor for neglect, increases the likelihood of children being placed in care (Sinha et al, ; Esposito, Chabot, Rothwell, Trocmé, & Delaye, ) and also reduces the likelihood of future reunification of these children with their families (Esposito et al, ).…”
Section: Introductionmentioning
confidence: 99%